INTEGRATION OF METALAXYL WITH TRICHODERMA HARZIANUM FOR THE CONTROL OF PYTHIUM DAMPING-OFF IN SUGARBEET - A N. MUKHOPADHYAY, INDU S. SAWANT AND (Indian Phytopathology, 2002)
A metalaxyl insensitive Trichoderma harzianum isolate (lMI No. 238493) was found antagonistic to Pythium aphanidermatum. This isolate hyperparasitised Pythium hyphae by coiling and direct penetration and also produced both volatile and non-volatile toxic metabolites. In glasshouse, T. harzianum growrn in media with different amounts of wheat bran: saw dust controlled damping-off o'f sugarbeet, in soil artificially infested with the pathogen. A linear correlation was obtained between rate of T. harzianum inoculum applied to the soil and degree of disease control. T. harzianum inoculum on sterilized wheat bran: saw dust substrate had no effect on sugarbeet seedlings. In field, soil application of 17.Sglm ridge of T. harzianum inoculum or seed treatment with 0.1 per cent metalaxyl provided 100 per cent disease control. Lower concentrations of both. T. harzianum and metalaxyl were less effective individually, but when used in combination, they had an additive effect providing 84-100 per cent disease control.